Family Resilience in Gampong Sungai Pauh: The Role of Emotional Regulation Strategies - Andriana, Fika; Muhammad Fadzl, Anis Irdina binti (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, human emotions should be well-managed to cope with life’s pressures, thereby creating harmony within families that supports family resilience. However, in reality, many individuals struggle to regulate their emotions, particularly in stressful situations, which often leads to family conflicts and threatens family stability, as observed in Gampong Sungai Pauh. The purpose of this study is to explore the strategies employed by the people of Gampong Sungai Pauh to regulate their emotions in stressful situations and to examine how emotional regulation affects family resilience. This research is classified as field research using a qualitative approach. The methodology employed is a phenomenological study. The findings reveal that the people of Gampong Sungai Pauh use various strategies to regulate their emotions, such as gathering with friends, refreshing themselves, seeking new activities, being patient, focusing on positive things, improving mental and spiritual well-being, and practicing solitude. However, the inability of some respondents to regulate their emotions has led to recurring conflicts, which negatively impact children and family stability.